Analisis Perubahan Tutupan Lahan Di Kawasan Pesisir Selatan Kota Sampang Dengan Menggunakan Citra Satelit Multitemporal Berbasis Sistem Informasi Geografis - Annafiyah, Ike Dayi F, Akh. Maulidi (Politeknik Negeri Madura, 2018)
Remote Sensing and the Geospatial Information System (GIS) can facilitate observation of land cover changes including land changes along the coast. With this technology, supervision and control of changes in coastal area becomes easier, faster, and more accurate. Remote sensing technology based on satellite imagery uses Landsat 8 imagery as a multi temporal image. Sampang, which is located in the coastal area of Madura island, is very important to accommodate land cover areas along its coast to maintain coastal environmental conditions. In this study, an observation of land cover changes was carried out based on supervised classification result of Landsat 8 images in 2014 and 2017. The result of this study show that the method can provide accurate information about land cover and its changes with Kappa accuracy value is 0.77 (Substantial agreement) and 0.82 (Almost perfect agreement). Additional area of Land use is a water body 0.61%, mangrove area 0.30%, dry land agriculture 10.63%, and bushes 6.80%. The reduction area is settlement of 0.21%, paddy fields of 18.11% and ponds of 1.85%.